Sistemática e Biogeografia de Ficus (Moraceae) na região Neotropical - Machado, Anderson Ferreira Pinto (2017)
Ficus L. (Moraceae), with approximately 750 species, is characterized by its typical inflorescence, the syconium or fig, a receptacle enclosed by bracts in a region called ostiole. Two lineages of the genus occur in the Neotropical Region, Ficus sect. Americanae (~ 100 species) and Ficus sect. Pharmacosycea (~ 20 species). The great diversity of the fig trees in the wet forests worldwide and the occurrence of species in all the Neotropical biomes make Ficus an interesting model to study the processes associated with diversification species in the Neotropical region. This work aimed to: contribute to the solution of taxonomic problems in Ficus sect. Americanae; to discover characters potentially relevant in taxonomy; to understand the process of species diversification in the Neotropics, helping to understand the history of diversity in this region. To accomplish to these goals, we use classical taxonomic procedures with analysis of the protologues and type collections, field work, morphological and anatomical studies as well as phylogenetic and biogeographical analyses. The results presented here are taxonomic novelties with the description of two new species, the establishment of two new names and the reestablishment of a species previously considered as a synonym. It is also is presented a key for species of Ficus sect. Americanae in the Mata Atlântica Domain. It is reported for the first time a specialization of the bracts surrounding the ostiole, as well as of the colleters in the inflorescences of the genus. The biogeographic approach showed that the diversification of the Neotropical fig trees began between the Oligocene and the Miocene and that the genus went through two bursts of diversification (in the Middle Miocene and Pliocene). Our results also showed that the hemiepiphyte habit and the reduced size of Ficus sect. Americanae allowed a greater diversification of this lineage in the Neotropics when compared to Ficus sect. Pharmacosycea.